IP spoofing defense: an introduction - Lee, Soon; Othman, Mohamed; Udzir, Nur Izura (2009)
In current Internet communication world, validity of source IP packet is and important issue. The problems of IP spoofing alarm the legitimate user of the Internet. This paper review recent progress of spoofing defenses by various researchers. Techniques and mechanisms proposed are being categorized to better illustrate the deployment and functionality of the mechanism. Overall, this paper summarizes the current anti spoofing mechanism in the Internet.